FEASIBILITY ANALYSIS OF DEVELOPING DRINKING WATER SUPPLY INFRASTRUCTURE PUBLIC PRIVATE PARTNERSHIP (PPP) SCHEME REVIWED FROM TECHNICAL, FINANCIAL, AND ECONOMIC ASPECTS (CASE STUDY: EASTERN REGION WATER SUPPLY SYSTEM, PERUMDA TIRTA RAHARJA) - Rizkia Nugraha, Iftikar
The development of a Water Supply System (SPAM) in a district or city is immensely beneficial for the prosperity of the people, particularly in improving public health and national economic growth by ensuring the provision of clean water services to the community at the lowest possible cost. As stated in Article 33, Paragraph 3 of the 1945 Constitution of Indonesia, the state is obligated to fulfill the basic rights and needs of its citizens within the framework of public services. The lack of access to clean drinking water is one of the most pressing issues in developing countries, including Indonesia, where only 44,94% of households had access to clean drinking water in 2022. The high leakage rate of 32,75% and 6,8% of households using water meters exacerbate the problem. These performance indicators do not align with the National Medium-Term Development Plan (RPJMN) 2015-2019, which aimed for 100% water supply coverage, continuous 24/7 water supply of at least 110 liters per person per day, 100% metering, and a maximum leakage rate of 25%. Considering these challenges, a funding of Rp. 123,5 trillion is required for the water supply sector development from 2020 to 2024, with Rp. 29,9 trillion allocated from Public-Private Partnership (PPP) sources. Given these circumstances, there is an opportunity for private sector collaboration with the government to develop the SPAM in accordance with Government Regulation No. 122 of 2015. To gather data, various methods such as field observations, literature studies, and questionnaires were utilized in the analysis of the study area's conditions. Two SPAM development schemes were created, meeting the applicable technical standards. These schemes were then compared, and the best scheme was selected using the Weighted Ranking Technique (WRT). Scheme 1, which involves a gravitybased distribution system with a total pipeline length of 457.760 meters and a total investment requirement of Rp. 906.552.803.000, was identified as the most technically feasible option. To assess the community's water supply needs and the local economic conditions, a Real Demand Survey (RDS) was conducted, involving 68 respondents from 9 districts. The RDS with 68 respondents showed a 71% Willingness to Connect (WTC), an Ability to Pay (ATP) of Rp. 156.176/month or Rp. 9.891/m3, and a Willingness to Pay (WTP) value of Rp. 131.000/month or Rp. 8.296/m3. These values are higher than the average tariff of Perumda. For the financial aspect, the system requires Operational Expenditure (Opex) in the first year, including raw water fee of Rp. 155/m3, electricity/energy cost of Rp. 15/m3, chemical cost of Rp. 255/m3, employee cost of Rp. 169/m3, and maintenance cost of Rp. 51/m3, along with administrative and general costs of Rp. 129/m3. These costs escalate by 4.71% annually, corresponding to the average 12-month inflation rate in Indonesia. Under this SPAM development scheme, the bulk water price at the source is Rp. 1,744/m3 in the first year, increasing by 28% every 4 years, in alignment with Perumda's tariff hike of 28.41% in 2022. Downstream, Perumda will charge an average tariff of Rp. 6,699/m3 starting from February 2023. Financial analysis indicates that the project is financially viable, with a Net Present Value (NPV) of Rp. 181,822,909,854 for the upstream and Rp. 425,165,224,594 for the downstream; Internal Rate of Return (IRR) of 14.41% for the upstream and 24.43% for the downstream; Benefit-Cost Ratio (BCR) of 3.4 for the upstream and 9.77 for the downstream. The payback period is 15 years for the upstream and 7 years for the downstream. Sensitivity analysis for both upstream and downstream scenarios shows that the system remains feasible even with a 10% increase in Capital Expenditure (Capex) and a 10% decrease in revenue, as well as a combination of both scenarios. Considering the results from the three aspects above, it can be concluded that the development of the Eastern Bandung District Water Supply System through a Public-Private Partnership scheme is deemed viable.